Şeyh Safî tezkîresinin Nişâtî tercümesi (inceleme - edisyon kritikli metin - 1a-265b - dizin - tıpkıbasım) - Çelik, Neslihan (My University, 2019)
Kültürün birinci asli unsuru dildir. Dil olmadan bir milletin kültüründen ve buna bağlıolarak da o milletin varlığından söz etmek mümkün değildir. Bir millete ait eserler, içindebulunulan sosyal şartların ve kültürün dil noktasında birer yansıması niteliği taşımaktadırlar.Benzer şekilde, Türk dili de Türk kültürünü yansıtmaktadır. Buna bağlı olarak da Türk diliyleyazılmış eserler incelenirken Türk kültürüne özgü bir şablon oluşturulmalı ve eserler buçerçevede değerlendirilmelidir.

The first element of culture is language. Without language, it is not possible to talk aboutthe culture of a nation and therefore the existence of that nation. The works of a nation are thereflection of the social conditions and culture in the language. Similarly, Turkish languagereflects Turkish culture. Accordingly, a template specific to Turkish culture should be createdand the works should be evaluated within this framework while examining the works written inTurkish language.
Keywords: History and criticism; Nishati’s Work Skeikh Safi Tezkire; St. Petersburg Copy; St. Petersburg Nüshası; Şeyh Safî Tezkîresi; Tabriz Copy; Tarih ve eleştiri; Tebriz Nüshası; Turkish Language; Turkish literature; TurkishCultural History; Türk Dili; Türk edebiyatı; Türk kültürtarihi